THE THERMAL PERFORMANCE OF MOSQUE WITH DOME ROOF AND TAJUK LIMASAN (Case study: Ottoman Mosques in Turkey and Java Mosques in Indonesia) - Sugini, Sugini; Fitriani, Amalia Nur; Anggoman, Fahrun Reza (DIMENSI (Journal of Architecture and Built Environment), 2017)
The purpose of this study are: (1) Analysing the thermal quality of the mosques which use dome and Tajuk &Limasan roof especially seen on the thermal pattern and behavior; (2) Knowing how high a proportion of openings may affect the quality of the indoor thermal. The study was conducted on the mosques in the two regions with different climates. The objects of research are (1)the Great Mosque of Banten, (2) Great Mosque of Yogyakarta,both of them located in Indonesia and(3) Sehzade Mosque , (4) Mihrimah Mosque, located in Turkey. Data were collected by observation and secondary data. For the first purpose data is processed into information about: (1) thermal quality in space, (2) the pattern of thermal comfort, (3) the distinctiveness of the pyramid roof and dome. For the second purpose, the measurements of the openings dimensions, temperature and humidity are done. In addition, the macro climate secondary data per year in each city are collected indirectly. Data processing is done by calculation, use the chart manually and using software Autodask Ecotect. The results of this study are as follows: (1) Tajuk & Limasan-roofed mosque had more varied radiation temperatures in each month, while the dome mosque has relatively stable. Tajuk& Limasan-roofed mosque has a homogeneous heat distribution across the roof. As for the dome-roofed mosque, spreading tends to diffuse; (2) the proportion of openings is more influential in the mosque located in the tropics (the Great Mosque of Banten-Indonesia) compared to the mosque located in a temperate climate (Sehzade Mosque-Turkey).